2018
DOI: 10.1038/nature25778
|View full text |Cite
|
Sign up to set email alerts
|

The genomic history of southeastern Europe

Abstract: Farming was first introduced to Europe in the mid-7th millennium BCE–associated with migrants from Anatolia who settled in the Southeast before spreading throughout Europe. To understand the dynamics of this process, we analyzed genome-wide ancient DNA data from 225 individuals who lived in southeastern Europe and surrounding regions between 12,000 and 500 BCE. We document a West-East cline of ancestry in indigenous hunter-gatherers and–in far-eastern Europe–early stages in the formation of Bronze Age Steppe a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
542
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 538 publications
(600 citation statements)
references
References 65 publications
44
542
2
12
Order By: Relevance
“…8.13). This fish hook was made with a newly introduced mechanical drilling technique (bow or pump drill) that might have arrived in the Danube Gorges area with migrant women who appeared at Lepenski Vir during the transition phase based on strontium isotope 25 and aDNA evidence 46 , and who might have transmitted to the indigenous population this new technique, a range of new osseous tool types (e.g. flat symmetrical awls with half-worked distal metapodial epiphysis manufactured from longitudinal halves [Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8.13). This fish hook was made with a newly introduced mechanical drilling technique (bow or pump drill) that might have arrived in the Danube Gorges area with migrant women who appeared at Lepenski Vir during the transition phase based on strontium isotope 25 and aDNA evidence 46 , and who might have transmitted to the indigenous population this new technique, a range of new osseous tool types (e.g. flat symmetrical awls with half-worked distal metapodial epiphysis manufactured from longitudinal halves [Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All this suggests that at this pivotal historical moment Lepenski Vir became an important hub of cultural exchanges and mixing between indigenous foragers and the first farming groups. Evidence that some of the individuals were buried inside trapezoidal buildings following typical Mesolithic rites of extended supine inhumations despite of their “pure” Anatolian Neolithic ancestry (AMS-dated burials 61 and 54e 46 , Fig. 4) may suggest that during this phase the power relationship was in favour of the indigenous forager community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…European Mesolithic hunter gatherers (WHGs) [8]. At the same time Eastern Europe was in the rudimentary stages of the formation of Bronze Age steppe ancestry, which later spread into Central and Northern Europe through East-West expansion [9].…”
Section: Anatolian Migrants European Ancestry Shows a Distinct West-mentioning
confidence: 99%
“…Further, we found significant association between the combination of WHG ancestry and 15 days' mean temperature and COVID-19 death/recovery ratio (R 2 =0.39, p=0.042). Previously it has been shown that European genomes evolved uniquely with regards to immune responsiveness, particularly pertaining to responses against viral infections [8]. Admixture with Neanderthals is believed to have introduced unique regulatory variants into European genomes, which likely modulated immune responses in European populations [7].We surmise that the European genome architecture has been extensively modulated by the complex origin and migration history of modern-day Europeans during Paleolithic, Mesolithic and Neolithic periods that in turn contributed via introduction of novel variants in European genomes.…”
Section: The European Storymentioning
confidence: 99%